Implementation of a longitudinal quality improvement curriculum for hematology/oncology fellows. Issue 28 (1st October 2022) - DiBenedetto, Samantha; Young, Philip; Mehra, Pooja; Hall, Richard Delmar; Keng, Michael Kenneth
Abstract : 315 Background: Quality improvement (QI) is an integral part of healthcare systems and an essential skill for trainees to develop. Education and engagement in QI activities is an ACGME core competency for GME trainees regardless of program or post-graduate year (PGY). There are many ways in which these competencies may be fulfilled and often vary widely between programs and institutions. Here we present the implementation of a longitudinal QI curriculum for hematology/oncology fellows at our institution. Methods: In July 2020 we implemented a 3-year longitudinal QI curriculum to meet criteria set forth by ACGME regarding QI training to improve fellow engagement in QI activities. The curriculum consists of 3 components: 1) introductory lectures on QI concepts and methodology including PDSA cycle and Lean Six Sigma, 2) monthly morbidity & mortality conferences utilizing root cause analysis to identify opportunities for improvement, and 3) fellow-initiated QI projects with regular feedback sessions. Fellows are encouraged to participate in ASCO's Quality Training Program (QTP) for further project development. A senior QI fellow is appointed to organize didactics and oversee project development. Milestones are set per training year. PGY1 fellows participate in didactics and feedback sessions to gain understanding of QI methodology and application to ongoing and future projects. PGY2 fellows develop and implement a project utilizing core QI principles. PGY3 fellows complete their longitudinal QI project, culminating in presentation and conference submission. At the conclusion of the curriculum, fellows are expected to achieve competency in 1) identifying clinical and institutional opportunities for QI, 2) understanding and applying QI concepts and methodology to project development, and 3) designing and implementing a QI project utilizing core concepts and methodology. Pre- and post-curriculum self-assessments will be used to evaluate knowledge of QI principles. Results: Since implementation fellows have actively participated in all components of the QI curriculum resulting in improved fellow satisfaction in QI education and engagement. Four fellow-initiated QI projects have been developed, resulting in 1 participation in ASCO QTP, 3 presentations at departmental grand rounds, and 3 abstract presentations at national meetings including ASH Annual Meeting, ASCO Annual Meeting, and ASCO Quality Symposium. Two projects have been completed, leading to interventions that have been implemented into routine practice at our institution. Conclusions: Implementation of a longitudinal QI curriculum at our institution has resulted in improved fellow experience in QI and successful implementation and presentation of QI projects at both the local and national levels. This curriculum has been well received by both fellows and faculty and has led to improved engagement in QI education and practices.